Barriers to adoption of improved agricultural technologies. A metanalysis for Africa. - Arslan, Aslihan; Floress, Kristin; Lamanna, Christine; Lipper, Leslie; Asfaw, Solomon; Rosenstock, Todd S. (2019)
Implementation of CSA technologies is seen as a cornerstone of improving agricultural productivity and resilience in Africa – so why is adoption so low? Many factors, both internal and external influence a farmer’s decisions.